Teaching the Inevitable: Embracing a Pedagogy of Failure - Eckstein, Lydia E.; Finaret, Amelia B.; Whitenack, Lisa B. (Teaching and Learning Inquiry, 2023)
Failure is often taken as a given in higher education, as an inevitable part of learning new things. Yet, it remains a part of learning that students tend to fear, and faculty tend to neglect. As faculty, we do not always strategize with or leverage our students’ struggles and failures for improved learning. Instead, we hope that students learn from their mistakes and study harder or try harder the next time, because moving on with material in class is necessary to meet learning objectives. In this article, we outline several strategies for using failure advantageously for promoting student growth and learning, and to minimize the stigma of struggle in academia. We make concrete suggestions and outline strategies and resources for faculty to incorporate a “pedagogy of failure” into their work with students and we describe structural barriers to using failure strategically in higher education. Click here to read the corresponding ISSOTL blog post.